The Teaching Interns' Use of Kinesics as Non-verbal Communication in the Classroom - Krisha Mae A. Caybot; April John M. Datoy; Arlyn S. Piit; Aris Pet Angeli A. Suarez; Alfer Jann D. Tantog (Journal of Elementary and Secondary School, 2024)
This study investigates the use of non-verbal communication, particularly kinesic behavior, by teaching interns during classroom instruction. The primary participants in this study are fourth-year teaching interns during the academic year 2022-2023 at a private higher education institution in Pagadian City, Philippines. The research approach employed is a case study with a qualitative methodology. The objective of this study is to examine the utilization of kinesics as a non-verbal communication tool by teaching interns in their interactions with students. It seeks to understand how teaching interns commonly employ kinesics and its perceived impact on students. Data for this study were gathered from various sources, including interviews conducted with ten teaching interns, feedback from three cooperating teachers, and insights from two students of the research participants. The findings indicate that the use of kinesics is beneficial for teaching interns. The incorporation of kinesics, such as postures, gestures, eye contact, and facial expressions, has created a dynamic classroom atmosphere and heightened students' engagement and the overall quality of instruction. It has positively influenced students' academic performance, leading to improved results and enhanced classroom behavior. Consequently, the integration of kinesics in the classroom supports effective communication between teaching interns and their students, resulting in clear and conducive instructional environments for learning.